Kristologi Kenotik sebagai Fondasi Formasi Spiritual dan Kepemimpinan Dalam Pendidikan S1 Teologi - Lucky Antonio; Edward Nimit Abraham (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
This study aims to analyze the role of kenotic Christology as a theological foundation for spiritual formation and non-dominative leadership in undergraduate theological education at STT Kerusso Indonesia. A quantitative survey design was employed, involving 26 students as respondents through a Likert-scale questionnaire. The results indicate that all measured variables are in the high category, with mean scores for kenotic Christology ranging from 4.10 to 4.30, spiritual formation at approximately 4.20, and non-dominative leadership at approximately 4.25. Correlation analysis shows strong positive relationships between kenotic Christology and spiritual formation (r≈0.65), as well as between spiritual formation and leadership (r≈0.70). Regression analysis further reveals a significant simultaneous contribution of 55%, indicating that the variables collectively support the formation of servant-oriented leadership. These findings confirm that kenotic Christology functions as a meaningful theological foundation in shaping spiritual habits, humility, self-emptying attitudes, and leadership practices that avoid domination. The study concludes that theological education should intentionally integrate kenotic values to strengthen spiritual maturity and servant leadership among future church leaders within academic communities that prepare students for humble ministry in diverse ecclesial contexts.